2023
DOI: 10.1364/prj.494932
|View full text |Cite
|
Sign up to set email alerts
|

Gate voltage control of helicity-dependent photocurrent and polarization detection in (Bi1−xSbx)2Te3 topological insulator thin films

Shenzhong Chen,
Jinling Yu,
Xiyu Hong
et al.

Abstract: Optical helicity provides us with an effective means to control the helicity-dependent photocurrent in the spin-momentum-locked surface states of topological insulators (TIs). Also, the TIs show potential in polarization detection as an intrinsic solid-state optical chirality detector for easier integration and fabrication. However, the complex photoresponses with the circular photogalvanic effect, the linear photogalvanic effect, and the photon drag effect in the TIs prevent them from direct chirality detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The HDPC current of the (Bi 0.7 Sb 0.3 ) 2 Te 3 nanoplate can be obtained by fitting the polarization-dependent photocurrent 057101-2 to the following equation: [4,11] J = J HDPC sin 2ϕ + L 1 sin 4ϕ + L 2 cos 4ϕ + j 0 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The HDPC current of the (Bi 0.7 Sb 0.3 ) 2 Te 3 nanoplate can be obtained by fitting the polarization-dependent photocurrent 057101-2 to the following equation: [4,11] J = J HDPC sin 2ϕ + L 1 sin 4ϕ + L 2 cos 4ϕ + j 0 .…”
Section: Resultsmentioning
confidence: 99%
“…The former one is due to the transfer of the angular momentum of the photon to the photo-generated carriers, while the latter one is owing to the transfer both of the angular momentum and the linear momentum of the photon to the photo-generated carriers. [11,[19][20][21][22] The bulk states of (Bi 1−x Sb x ) 2 Te 3 nanoplates belong to D 3d symmetry group, which will not generate CPGE current, and the CPGE current can only come from the surface states or the two-dimensional electron gas (2DEG) of the (Bi 1−x Sb x ) 2 Te 3 nanoplates, which have a symmetry of C 3v . [1] By measuring the HDPC current under ionic liquid top-gate voltage, it is revealed that the HDPC is mainly contributed by the surface states rather than the 2DEG (see the discussion below).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations